Does hip implant positioning affect the peak external adduction moments of the healthy knees of subjects with total hip replacements?1. Issue 8 (21st March 2013) - Foucher, Kharma C.; Wimmer, Markus A.
Abstract After unilateral total hip replacement (THR) for hip osteoarthritis (OA), knee OA incidence or progression is common. The contralateral knee is at particular risk, and some have speculated that abnormal THR‐hip biomechanics contributes to this asymmetry. We investigated the relationships between operated‐hip joint geometry or gait variables and the peak external knee adduction moments—an indicator of knee OA risk—in 21 subjects with unilateral THRs. We found that the peak adduction moment was 14% higher on the contralateral versus the ipsilateral knee (p = 0.131). The best predictors of ipsilateral knee adduction moments were superior‐inferior joint center position and operated‐hip peak adduction moment (adj R2 = 0.291, p = 0.017). The sole predictor of the contralateral knee adduction moment was the medial‐lateral hip center position (adj R2 = 0.266, p = 0.010). A postoperative medial shift of the hip center was significantly correlated with a lower postoperative contralateral/ipsilateral knee adduction moment ratio (R = 0.462, p = 0.035). Based on these relationships, we concluded that implant positioning could influence the biomechanical risk of knee OA progression after THR. Although implant positioning decisions are necessarily driven by other factors, it may be appropriate to assess individual THR candidate's knee OA risk and adjust perioperative management accordingly. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:1187–1194, 2013